Global liquidity, risk premiums and growth opportunities - De Nicoló, Gianni; Ivaschenko, Iryna V. (IMF working paper ;, 2009)
This paper constructs new indicators of liquidity for equity, bond and money markets in major advanced and emerging market countries, documents their evolution and comovements, and assesses the extent to which such measures are determinants of selected spreads and proxy measures of countries' growth opportunities. Three main results obtain. First, there is evidence of an historical increase in market liquidity since the early 1990s, in part as a result of advances in international financial integration, but markets have been increasingly exposed to global systemic liquidity shocks. Second, liquidity indicators appear to be important determinants of bond spreads in advanced economies and EMBI spreads in emerging markets. Third, improvements in market liquidity have significant real effects, as liquidity indicators have a significant positive impact on proxy measures of countries' growth opportunities.